5(k-2)-6=4k-(3k-1)

Simple and best practice solution for 5(k-2)-6=4k-(3k-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(k-2)-6=4k-(3k-1) equation:


Simplifying
5(k + -2) + -6 = 4k + -1(3k + -1)

Reorder the terms:
5(-2 + k) + -6 = 4k + -1(3k + -1)
(-2 * 5 + k * 5) + -6 = 4k + -1(3k + -1)
(-10 + 5k) + -6 = 4k + -1(3k + -1)

Reorder the terms:
-10 + -6 + 5k = 4k + -1(3k + -1)

Combine like terms: -10 + -6 = -16
-16 + 5k = 4k + -1(3k + -1)

Reorder the terms:
-16 + 5k = 4k + -1(-1 + 3k)
-16 + 5k = 4k + (-1 * -1 + 3k * -1)
-16 + 5k = 4k + (1 + -3k)

Reorder the terms:
-16 + 5k = 1 + 4k + -3k

Combine like terms: 4k + -3k = 1k
-16 + 5k = 1 + 1k

Solving
-16 + 5k = 1 + 1k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
-16 + 5k + -1k = 1 + 1k + -1k

Combine like terms: 5k + -1k = 4k
-16 + 4k = 1 + 1k + -1k

Combine like terms: 1k + -1k = 0
-16 + 4k = 1 + 0
-16 + 4k = 1

Add '16' to each side of the equation.
-16 + 16 + 4k = 1 + 16

Combine like terms: -16 + 16 = 0
0 + 4k = 1 + 16
4k = 1 + 16

Combine like terms: 1 + 16 = 17
4k = 17

Divide each side by '4'.
k = 4.25

Simplifying
k = 4.25

See similar equations:

| 3(c+1)=9 | | 3x-15y=7 | | 5x-17+48=180 | | 15y+21-3y=1/3(9y+15)+(9y+16) | | 43-(x+7)=9x-4 | | x+(-56)= | | x^9=5 | | 42y+6=14+2y-25y^2 | | 19-h=32 | | y=2x^2-4x+2 | | 0.25=x-x^2 | | Y^2-4y-30=0 | | x^2-x-41=0 | | 19u-14u=5 | | x*2x=2 | | x+2x=2 | | 3x+7=-6x+2 | | 1/3x+12-8=4x+12 | | 3t-2t=13 | | 2r-r=11 | | 4x+6x+16=2(2x+8+3x) | | x-25000=100 | | 17s-14s=15 | | x^2-80=6x | | 2x+3x+4=4x+12+x | | 7x-12-3x+4-4x=15 | | 3-9x=-60 | | 2x*2x=18 | | 3w^2+3w=4w^2+4 | | h+3=12 | | 1.7*100+x=825 | | -2(f+3)=3(5-3f) |

Equations solver categories